Working Capital Management and Firms' Profitability (A Study of Selected Consumer Goods Manufacturing Companies in Nigeria): Array - Mache, Vanessa Onyinyechukwu; Omodero, Cordelia Onyinyechi (Acta Universitatis Danubius. Œconomica, 2021)
ABSTRACT The importance of working capital management cannot be overstated since ineffectiveness leads to corporate bankruptcies all over the world. The purpose of the research was to see how working capital management affects the profitability of companies in Nigeria's consumer goods manufacturing sector. For a period of six years, relevant secondary data was collected from published annual reports of the 16 publicly traded firms under investigation between 2014-2019. The analysis approach used in this study was the panel least square regression model, which was combined with the Pearson's correlation model. The findings of the research demonstrate that the cash conversion cycle (CCC) has no effect on profitability. The study also discovered that inventory conversion cycle (ICC) and profitability have a negative and significant association, whereas average payment period (APP) and profitability have a negative and insignificant connection. Managers should pay close attention to the working capital components, as shown by this study, to eliminate inefficiency and guarantee optimal levels.